Deskripsi Tingkat Self Confidence Remaja - Nur Arienza, Della; ., Indah Fajrotuz Zahro (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to determine the description of the level of Self Confidence of adolescents. 52 adolescents with random sampling techniques are subjeks in the study. The research method is descriptive quantitative. The Self Confidence Scale is a Likert scale of 50 statements divided into favorable and unfavorable items with alternative answers strongly agree, agree, disagree and strongly disagree which are arranged from the Lauser concept, namely aspects of independence, commitment, self-understanding, self-adjustment, assertiveness, optimism and daring to express opinions. Researchers use a used tryout scale. Validity test with product moment technique and reliability test using alpha cronbach technique with SPSS 26.00 application. From the validity test, 37 valid items were obtained while the results of the reliability test were 0.925 including strong reliability. The range of the Self Confidence level group of Sumerrejo Bojonegoro adolescents is a high group of 8 adolescents, medium group of 40, low group of 4 adolescents. The results of this study recommend that adolescents continue to improve their Self Confidence.